The Model for Thais Physician Competency Development Based on Focus Discussion Group (FDG): A Review - Pingmuang, Chutima; Sirisunhirun, Somboon; Ekhwan Toriman, Mohd; ., . (International Journal of Engineering and Technology, 2018)
Current changes and priorities in the country regarding population patterns and health care programs will require reforms in older health care and the increasing incidence of chronic diseases. In this study, the data was collected using with a systematic-purposive sampling using the snowball Delphi technique, key informants comprising 21 experts were selected from the Medical Council of Thailand, the Medical Association of Thailand and Health Systems Research Institute (HSRI). The tools used in this research include in-depth interview, the Likert scale with five-level Likert items for measuring the dispersion and congruence of consensus, and the Likert scale with three-level Likert items for content validity which is analyzed using the items of objectives congruence (IOC), the median (MD) and the quartile deviation (QD). The results show to be both valid and reliable for measuring physiciansâ€™ competency in Thailand. The results of the competency-based instrument can be used as of to be the healthcare public policy to encourage and guide regarding healthcare agencies to modify their competency according to the evaluation criteria, and also cultivate physicians with strong knowledge and skills, innovation and redesign the curriculum in medical schools inevitably. Overall, the level of physicianâ€™s desirable competency will be increased in Thailand. Â Â